2014
DOI: 10.3389/fimmu.2014.00170
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing a B-Cell Clonal Lineage. II. Mutation, Selection, and Affinity Maturation

Abstract: Affinity maturation of the antibody response is a fundamental process in adaptive immunity during which B-cells activated by infection or vaccination undergo rapid proliferation accompanied by the acquisition of point mutations in their rearranged immunoglobulin (Ig) genes and selection for increased affinity for the eliciting antigen. The rate of somatic hypermutation at any position within an Ig gene is known to depend strongly on the local DNA sequence, and Ig genes have region-specific codon biases that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 36 publications
2
120
0
Order By: Relevance
“…Previous research on patients with celiac disease has revealed limited SHMs in autoreactive plasma cells (12), which may be indicative of low-affinity Ag binding (32). In this study, limited SHMs in class-switched isotypes were also observed in PBC patients and their subgroups.…”
Section: Discussionsupporting
confidence: 63%
“…Previous research on patients with celiac disease has revealed limited SHMs in autoreactive plasma cells (12), which may be indicative of low-affinity Ag binding (32). In this study, limited SHMs in class-switched isotypes were also observed in PBC patients and their subgroups.…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, amino acid substitutions in CH235 at these positions were also frequently seen in non-HIV-1 antibodies (16). These commonalities extended to other V H 1-2*02 and V H 1-46 CD4 mimic bnAbs (16) and V H 1-2*02 V3-glycan bnAbs (Bonsignori M. et al, submitted), implying that intrinsic mutability at specific nucleotide sites is a more general biological phenomenon that plays a role in dictating the degree of somatic mutations (16, 32, 65, 66). …”
Section: Antibody-virus Co-evolutionmentioning
confidence: 85%
“…Isolated Ig genes were analyzed using a Bayesian method (20). The estimated mutation frequency of the heavy chains (HCs) of Env-reactive mAbs was 9.3% ( Figure 4F); this mutation frequency was higher than that observed for Env-reactive antibodies isolated from humans immunized 4 times in the GSK PRO HIV-002 trial (3.8%; ref.…”
Section: M-r)mentioning
confidence: 93%